Knowledge, Attitude, Practice, and Barriers of Adverse Drug Reaction Reporting Among Healthcare Professionals in Timor‐Leste: A Cross‐Sectional Survey - Juanina daCosta; Wichit Nosoongnoen; Watcharee Rungapiromnan; Pramote Tragulpiankit (Clinical and Translational Science)
ABSTRACT The Timor‐Leste Pharmacovigilance (PV) became an associate member of the WHO Programme for International Drug Monitoring in 2019; however, the adverse drug reaction (ADR) reporting rate remains low, with only nine reports per 1342 million inhabitants over 5 years. This study aimed to evaluate the knowledge, attitude, practice, and barriers related to ADRs, pharmacovigilance, and ADR reporting among healthcare professionals (HCPs) in Timor‐Leste. A cross‐sectional survey with a validated, self‐administered questionnaire was conducted among 600 HCPs, including clinical doctors, nurses, and pharmacy employees from one national referral and five referral hospitals. Of the 461 HCPs who responded (76.8% response rate), 98 were clinical doctors (21.3%), 311 nurses (67.4%), and 52 pharmacy employees (11.3%). The knowledge score on ADRs was 3.81 ± 0.36 out of 8, with clinical doctors, nurses, and pharmacy employees scoring 4.49 ± 0.51, 3.47 ± 0.24, and 4.56 ± 0.26, respectively. On pharmacovigilance and ADR reporting, the score was 3.00 ± 0.16 out of 8, with clinical doctors, nurses, and pharmacy employees scoring 3.36 ± 0.26, 2.81 ± 0.08, and 3.50 ± 0.24, respectively. All scores referred to the number of correctly answered questions. Positive attitudes were observed, with 53.4% agreeing that ADR reporting is crucial for drug safety, although only 22.0% reported observed ADRs. Key barriers included unavailability of reporting forms (81.0%), insufficient financial support (71.9%), and lack of reporting by colleagues (71.4%). These findings highlight the need for increased awareness, training, and resources to improve ADR reporting in Timor‐Leste.